Aboriginal youth mentoring: a pathway to leadership - Mishel McMahon; Michael Chisholm; Werner Vogels; Corina Modderman (2024)
Abstract: This article shares findings from evaluating a mentoring programme for Aboriginal youth on Yorta Yorta (an Aboriginal Tribal nation, north-eastern Victoria and Southern New South Wales, Australia) Country. This work is positioned in First Nations worldviews that are relational and require deep listening to youth, mentors, Elders, Country, and Ancestors. Applying a qualitative participatory action research design, methods involved attending camps on Country and research Yarning Circles. The findings demonstrate that Aboriginal mentoring programmes need to be led in their delivery and evaluation by First Nations peoples. This ensures that the programmes are culturally embedded in First Nations worldviews and that important interpretations of meanings are not overlooked. On Country experiences are a place for healing and learning. Country is a stakeholder in Aboriginal mentoring programmes. A trusting mentoring relationship creates a space where youth become part of an Aboriginal community, and where they feel strong in their identity.